2004
DOI: 10.1016/j.jcis.2003.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of bilayers and multilayers of cationic and anionic co-polymers of acrylamide on silicon oxide

Abstract: Silica surfaces were consecutively treated with copolymers of cationic and anionic polyacrylamides (C-PAM and A-PAM, respectively) and the layer-by-layer build-up was continuously monitored with the aid of stagnation point adsorption reflectometry (SPAR). Four different charge densities of the cationic polymer and one charge density of the anionic polymer were studied. The solid substrate used in the investigation was an oxidized Si wafer, the charge of which was varied by performing the measurements at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
(53 reference statements)
3
36
0
Order By: Relevance
“…On the other hand, the dissipation increased after PGA and decreased after PAH addition in accordance with the literature (Wagberg et al, 2004;Boulmedais et al, 2003;Grieshaber et al, 2008). This indicates a more rigid film in case of PAH being added the last (Figure 3a).…”
Section: Polyelectrolyte Multilayersupporting
confidence: 92%
“…On the other hand, the dissipation increased after PGA and decreased after PAH addition in accordance with the literature (Wagberg et al, 2004;Boulmedais et al, 2003;Grieshaber et al, 2008). This indicates a more rigid film in case of PAH being added the last (Figure 3a).…”
Section: Polyelectrolyte Multilayersupporting
confidence: 92%
“…So-called linear [4] or exponential [5,6] growth rates were frequently described from the change of output in different analytical measurements, but they were scarcely discussed in terms of mass uptakes, due to difficulties in scaling the instrumental output. In the case of charge densities, results cover a wide range between approximately a 1/1 polymer stoichiometry [7,8] three fold excess of the cationic polymer [9] for the same polymers pair as in Ref. [7], and intermediate cases [10].…”
Section: Introductionmentioning
confidence: 87%
“…Despite the fact that the theory and subsequent conversion of raw data to adsorbed amount are based on a one-layer adsorption model, it has previously been shown that optical reflectometry can yield valuable information on the kinetics of PEM formation [8,20,21]. A full description of the equipment and the underlying theory of its use is given by Dijt et al [22].…”
Section: Stagnation Point Adsorption Reflectometry (Spar)mentioning
confidence: 99%